Application Of Omni-Channel Strategy In Optimizing The Supply Chain Digitalization Process In Indonesia (Case Study: PT X) - Putra, Reinardus Andoni Nasera; Prihardianto, Rahaditya Dimas; Arismawati, Paramaditya (Dinasti Publisher, 2024)
PT X is a staple food producer company that employs a make-to-stock (MTS) production strategy. In the implementation of MTS used by PT X, customer needs are met through the sale of ready-made product stocks. The advent of the digitalization era has introduced new strategies that can be applied in the development of the supply chain, particularly in Indonesia. To achieve success in the digitalization process, the omnichannel function involves integrating online and offline channels and providing real-time information and services to customers to enhance their engagement. A profound understanding of omnichannel implementation is required, and this research utilizes a game theory approach as a tool to assess the success of omnichannel. Subsequently, a comparison of the best strategies generated in the game theory modeling needs to be conducted. The aim of this research is to enable companies to have a strategy in digitalization implementation to be more responsive to market changes and meet the increasing expectations of customers. However, to achieve success in omnichannel implementation, companies need to invest and commit to facing challenges and optimizing opportunities offered by this strategy.